Entomological and Molecular Surveillance of Anopheles Mosquitoes in Freetown, Sierra Leone, 2019 - Zhao, Ning; Sesay, Ishaq; Tu, Hong; Yamba, Frederick; Lu, Liang; Guo, Yuhong; Song, Xiuping; Wang, Jun; Liu, Xiaobo; Yue, Yujuan; Wu, Haixia; Liu, Qiyong (Frontiers in Public Health, 2021)
Abstract Background: Malaria is endemic in Sierra Leone, with stable and perennial transmission in all parts of the country. At present, the main prevention and control measures of mosquito vectors in Sierra Leone are insecticide treated nets (ITN) and indoor residual spraying (IRS). Notably, the most recent entomological surveillance was carried out prior to the civil war, between 1990 and 1994. Therefore, a new entomological surveillance needs to be carried out to support targeted malaria control strategies. Methods: Anopheles mosquitoes were collected between June and December 2019 using the light trap method. From these, we conducted species identification, analyzed seasonal fluctuation and Plasmodium infection rate, and monitored insecticide resistance. Results: Surveillance of seasonal fluctuation showed that there were two periods of peak Anopheles density in July (mean 13.67 mosquitoes/trap/night) and October (mean 13.00 mosquitoes/trap/night). Meanwhile, the lowest of the Anopheles density occurred in early September. Ninety-one representatives of Anopheles gambiae s.l. were selected and identified as An. gambiae s.s. (35 M forms and 56 S forms) using PCR. Anopheles gambiae s.s. were found to be heterozygous resistant to the knockdown resistance (kdr) L1014F mutation (100%). Meanwhile, the East African mutation (kdr L1014S) was absent in the tested mosquitoes. Three mosquitoes that tested positive for the parasite, P. falciparum had an individual P. falciparum infection rate of 12.50%, 16.67%, and 14.29%, respectively. The sampling dates of positive mosquitoes were distributed in two peaks of mosquito density. Conclusion: This study identified the dominant Anopheles species in Freetown as An. gambiae and the predominant species within the An. gambiae complex was An. gambiae s.s. Surveillance of seasonal fluctuations and high P. falciparum infection rates in Anopheles indicate that the alternation of drought and rainy seasons from June to July, and from October to November, are the key periods for malaria control and prevention in Freetown, Sierra Leone. The high frequency of kdr allele mutation in Anopheles gambiae calls for close monitoring of vector susceptibility to insecticides and tracing of resistance mechanisms in order to develop more effective vector control measures and strategies.